(untitled) (Cardiovascular Journal, 2016)
Background: The presence of anomalous muscle bundles may pro-duce a pressure gradient between the inflow and outflow portions of the right ventricle, resulting in double-chambered right ventricle. We reviewed the outcomes of double chambered right ventricle surgical repair. Methods: Between December 2012 and January 2014, 6 patients under went surgical repair of a double-chambered right ventricle. The patients ranged in age from 3 years to 20 years (mean 8.2±5.9 yrs). Right ventricular outflow tract pressure gradients were from 60 to 120 mm Hg (mean 63.3±40.3). An associated ventricular septal defect was present in 4 patients (66.66%). Results: There were no hospital or late deaths. Mean postsurgical follow up was 3.8±0.8 months). No patient required further surgery to relieve obstruction of right ventricular outflow tract. Conclusions: Surgical repair of a double chambered right ventricle yield excellent hemodynamic and functional results. Cardiovasc. j. 2016; 8(2): 165-168